Implementasi Kebijakan Peraturan Daerah Nomor 6 Tahun 2009 Tentang Rencana Tata Ruang Wilayah Kabupaten Sidoarjo (Studi Alih Fungsi Lahan Sawah di Kecamatan Wonoayu Kabupaten Sidoarjo) - Mohamad Hatta Karuniawan; Luluk Fauziah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
The purpose of this study was to describe the process of Implementation Local Regulation number 6 of 2009 on the Spatial Planning related to conversion of paddy fields in the Wonoayu District, Sidoarjo regency, describe the role of actors and its inhibiting and supporting factors. This research used qualitative descriptive methods. The result study showed that Policy Implementation of Local Regulation number 6 of 2009 the Spatial Planning related to conversion of paddy fields in the Wonoayu District, Sidoarjo regency wasn’t run yet. Thus, it resulted a chance for certain stakeholders to more concerned of profitable personal and group interests than society interests. Some of the actors that are involved in this policy implementation among other investors, communities, and governments have each role and synergize with each other. However, in reality this policy implementation was not independent of the supporting factors such ideal and good human resources and legal sanctions for violators of the rules. In addition inhibiting factors included the lack of communication that exists between the government and the landowners as well as supervision only as formality.